DIGGING TIME DECREASION ON THE BLASTING OF OVERBURDEN; EXPLOSION GEOMETRY OVERVIEW - Amri, Nur Ali; Keenlie, Michael; Hariyanto, Raden; Muhammadi, Berryl Afkar (Journal TECHNO, 2023)
This study aimed to evaluate the geometric design the P80 or Passing 80% of rock fragments and the digging time of equipment for sandstone overburden blasting with rock density, 2.43 kg/m3. As a basis for the results of observations on the current geometric design with a burden of 9 m, spacing of 9 m, and a depth of blast holes of 8 m, problems were found in the results of rock fragments that did not meet the criteria with the size of the rock fragments P80, 79.24 cm, the digging time of loading, 13.03 second and an average powder factor of 0.24 kg/m3. To obtain more uniform rock fragments is to improve the blasting geometry, so the energy distribution can be even that rock fragments and better digging time can be obtained in sandstone. The blasting geometry design which is proposed to improve fragmentation, 8 m; burden, 9 m; spacing; 3.5 m stemming; and 8 m blast hole depth with a column filled explosives of 4 m and the number of perforated explosives is 163.2 Kg, with powder factor, 0.28 kg/m3. The proposed blasting geometry produces suitable rock fragment. P80 is 39.93 cm and average digging time of 10.61 seconds.